PENGARUH LIKUIDITAS DAN SOLVABILITAS DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATOR TERHADAP HARGA SAHAM PADA BANK UMUM PEMERINTAH YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2018 - Nasruddin Nasruddin; Mardiana Mardiana (Jurnal Interprof, 2021)
The study was conducted to determine the effect of the Current Ratio on Stock Prices in the Government banking sub-sector (BUMN Persero) on the Indonesia Stock Exchange during 2015-2018. The results of the Moderated Regression Analysis (MRA) test on the Current Ratio variable to the Stock Price moderated by the Return on Equity variable have an R Square value of 0.294 or 29.4%, in which the R Square value has increased by 0.06 or 6% from before moderation. From these results it can be seen that the variable Return on Equity can strengthen or increase the influence of the Current Ratio variable on stock prices. While the results of the Moderated Regression Analysis (MRA) test on the Debt to Equity Ratio variable against the Stock Price moderated by the Return on Equity variable have an R Square value of 0.548 or 54.8%, in which the R Square value has increased by 0.126 or 12. 6% from before moderation. From these results it can be seen that the variable Return on Equity can strengthen or increase the influence of the Debt to Equity Ratio variable on stock prices.